2008
DOI: 10.1128/jvi.02250-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Cytotoxicity of Epstein-Barr Virus (EBV) Latent Membrane Protein 1 (LMP1) in EBV Latency III B Cells: LMP1 Induces Type II Ligand-Independent Autoactivation of CD95/Fas with Caspase 8-Mediated Apoptosis

Abstract: The Epstein-Barr virus (EBV) oncoprotein latent membrane protein 1 (LMP1) is thought to act as the major transforming protein in various cell types, by rerouting the tumor necrosis factor receptor family signaling pathway. Despite this implication in EBV-associated transformation of cells, LMP1 toxicity is a well-known but poorly studied feature, perhaps because it contradicts its role in transformation. We show that LMP1 physiological levels are very heterogeneous and that the highest levels of LMP1 correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 62 publications
(83 reference statements)
2
34
0
1
Order By: Relevance
“…Consistent with the results of the present study, Kijima et al (14) knocked-down the LMP1 gene in NPC cells and identified that the cleavage of caspase-3 and -8 and poly(ADP-ribose) polymerase 1 was increased. However, in another study, LMP1 activated caspase-8, -9, -3 and -7 via the induction of Fas overexpression in lymphoblastoid cell lines (32). The inconsistencies observed between these studies may be attributed to the dual effects of LMP1 to induce apoptosis, which was also observed in the study conducted by Chen and Chen (33).…”
Section: Discussionmentioning
confidence: 37%
“…Consistent with the results of the present study, Kijima et al (14) knocked-down the LMP1 gene in NPC cells and identified that the cleavage of caspase-3 and -8 and poly(ADP-ribose) polymerase 1 was increased. However, in another study, LMP1 activated caspase-8, -9, -3 and -7 via the induction of Fas overexpression in lymphoblastoid cell lines (32). The inconsistencies observed between these studies may be attributed to the dual effects of LMP1 to induce apoptosis, which was also observed in the study conducted by Chen and Chen (33).…”
Section: Discussionmentioning
confidence: 37%
“…In relation to this point, the FR sequence is also known to be critical for the upregulation of EBV latent membrane protein-1 (LMP-1) promoter (6). The truncated FR (FR20) may result in the overstimulation of the LMP-1 promoter and the overproduction of the LMP-1 protein, which may be disadvantageous for B-cell transformation due to its cytostatic or cytotoxic effects (4,8,20). Presumably, the preservation of the full-length FR (FR29) is important for the appropriate expression levels of viral transforming genes in addition to its contribution to the episomal persistence of the complete EBV genome.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with the highest level of LMP1 have enhanced MHC class I expression and are preferentially killed by T cells in vitro (14). In addition, LMP1 activates CD95 expression, promoting FAS-mediated killing by T cells (17). Moreover, LMP1 induced early-onset B cell lymphomas in a recent LMP1 transgenic mouse model only when T cell function was inhibited, since LMP1 + B…”
Section: Introductionmentioning
confidence: 99%